A high strength cable and a method of making the same
Patent Information
- Application Number
- CN202610974336.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-09-01
AI Technical Summary
[0004]针对以上技术问题,本发明提供了一种高强度电缆及其制备方法,本发明提供的增韧剂提高了电缆低温下的断裂伸长率,解决了现有电缆耐低温性不足的问题
[0015] Compared with the prior art, the present invention provides a high-strength cable. First, a compound of polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester is added to the outer sheath, which improves the elongation at break of the cable outer sheath at low temperatures. Among them, the polyolefin elastomer, as a tough skeleton, has excellent compatibility with the matrix and can form a more continuous structure in the matrix. The liquid terpene resin and rosin triethylene glycol ester can penetrate into the molecular chains of the polymer, significantly reducing the glass transition temperature of the material at low temperatures, so that it still has a certain degree of flexibility at low temperatures. Furthermore, the rosin triethylene glycol ester can improve the interfacial bonding force between the filler and the matrix, ultimately significantly improving the elongation at break of the cable outer sheath at low temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, specifically to a high-strength cable and its manufacturing method. Background Technology
[0002] High-strength cables are crucial for ensuring the safe operation of power transmission and various rail transit systems. Currently, these cables often use materials such as polyethylene and polyvinyl chloride as their outer sheath to meet the requirements for strength and abrasion resistance.
[0003] However, in cold and frigid regions, these materials are more prone to hardening and embrittlement, resulting in decreased flexibility and increased susceptibility to cracking when bent or stretched. This affects their insulation and protective performance, making them unsuitable for long-term use in cold regions. Therefore, there is an urgent need to develop cables with superior low-temperature resistance. Summary of the Invention
[0004] To address the above technical problems, this invention provides a high-strength cable and its preparation method. The toughening agent provided by this invention improves the elongation at break of the cable at low temperatures, thus solving the problem of insufficient low-temperature resistance of existing cables.
[0005] The specific technical solution of the present invention is as follows: According to one aspect of the present invention, a high-strength cable is provided, comprising a conductor, an insulation layer, and an outer sheath arranged sequentially from the inside to the outside; the outer sheath comprises the following raw materials: polyethylene, ethylene-vinyl acetate copolymer, filler, toughening agent, lubricant, antioxidant, ultraviolet absorber, and coupling agent; The toughening agent includes polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester.
[0006] In the above technical solution, the mass ratio of the polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester is 6.5:2:1.2~1.5.
[0007] In the above technical solution, the outer sheath comprises the following raw materials in parts by weight: 70-85 parts of polyethylene, 18-24 parts of ethylene-vinyl acetate copolymer, 15-20 parts of filler, 8-14 parts of toughening agent, 0.8-1.6 parts of lubricant, 0.4-0.8 parts of antioxidant, 0.3-0.7 parts of ultraviolet absorber, and 0.8-1.5 parts of coupling agent.
[0008] In the above technical solution, the filler includes one or more of needle-shaped wollastonite powder, aluminum silicate fiber powder, barium sulfate, and fly ash beads.
[0009] In the above technical solution, when the filler includes needle-shaped wollastonite powder, aluminum silicate fiber powder and fly ash beads, the mass ratio of the needle-shaped wollastonite powder, aluminum silicate fiber powder and fly ash beads is 5:3:1.5~2.5.
[0010] In the above technical solution, the lubricant includes one or more of calcium stearate, zinc stearate, and stearic acid.
[0011] In the above technical solution, the antioxidants include antioxidant 1076 and antioxidant 168.
[0012] In the above technical solution, the ultraviolet absorber includes one or more of ultraviolet absorber UV-531, ultraviolet absorber UV-327 and ultraviolet absorber UV-328.
[0013] In the above technical solution, the coupling agent includes a silane coupling agent.
[0014] According to another aspect of the present invention, the present invention also provides a method for preparing the above-mentioned high-strength cable, comprising the following steps: An insulating layer is formed on the outside of the conductor to obtain the wire core; polyethylene, ethylene-vinyl acetate copolymer, coupling agent, filler, toughening agent, antioxidant, ultraviolet absorber and lubricant are added in sequence and mixed, and then extruded onto the surface of the wire core to obtain a high-strength cable.
[0015] Compared with the prior art, the present invention provides a high-strength cable. First, a compound of polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester is added to the outer sheath, which improves the elongation at break of the cable outer sheath at low temperatures. Among them, the polyolefin elastomer, as a tough skeleton, has excellent compatibility with the matrix and can form a more continuous structure in the matrix. The liquid terpene resin and rosin triethylene glycol ester can penetrate into the molecular chains of the polymer, significantly reducing the glass transition temperature of the material at low temperatures, so that it still has a certain degree of flexibility at low temperatures. Furthermore, the rosin triethylene glycol ester can improve the interfacial bonding force between the filler and the matrix, ultimately significantly improving the elongation at break of the cable outer sheath at low temperatures. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of this invention more apparent, the invention is described in detail below. It should be understood that the invention is not limited to the description herein.
[0017] polyethylene The polyethylene used in this invention is the type of polyethylene known in the art for use in cable outer sheaths. In the outer sheath of this invention, polyethylene serves to provide the main structural framework of the material, giving the outer sheath a certain mechanical strength and rigidity. It is the main continuous phase and strength-supporting component in the outer sheath.
[0018] Ethylene-vinyl acetate copolymer The ethylene-vinyl acetate copolymer used in this invention is a known ethylene-vinyl acetate copolymer that can be used for cable outer sheaths. In the outer sheath of this invention, the main function of the ethylene-vinyl acetate copolymer is to improve the compatibility between the inorganic filler and the matrix, and to reduce agglomeration.
[0019] filler The filler in this invention includes one or more of the following: acicular wollastonite powder, aluminosilicate fiber powder, barium sulfate, and fly ash beads. When acicular wollastonite powder, aluminosilicate fiber powder, and fly ash beads are used in combination, the tensile strength of the cable outer sheath is improved even more. The acicular wollastonite powder and aluminosilicate fiber powder, acting as a fibrous reinforcing skeleton, can effectively transfer stress and prevent crack propagation during tension. The fly ash beads, being smooth microspheres, can improve the dispersibility of the filler in the matrix and fill the gaps between fibers, thus enhancing the filler's packing properties. The denser packing reduces internal defects, resulting in higher tensile strength for the cable outer sheath. The mass ratio of needle-shaped wollastonite powder, aluminosilicate fiber powder, and fly ash beads is 5:3:1.5~2.5, preferably 5:3:2. At this ratio, the tensile strength of the cable outer sheath is further improved. When the proportion of fly ash beads in the filler is low, the filling capacity is reduced, and voids are more likely to appear. When the proportion of fly ash beads is high, the fly ash beads will reduce the continuity of the reinforcing skeleton, ultimately weakening the tensile strength of the cable outer sheath.
[0020] toughening agent In this invention, the toughening agent selected is a combination of polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester, which improves the elongation at break of the cable outer sheath at low temperatures. Furthermore, when the mass ratio of polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester is 6.5:2:1.2~1.5, the synergistic effect is further enhanced. When the proportion of polyolefin elastomer is low, the toughness of the outer sheath is insufficient, and it is prone to brittleness at low temperatures. When the proportion of polyolefin elastomer is high, the interfacial bonding force between the filler and the matrix decreases.
[0021] lubricant The lubricant used in this invention is a lubricant known in the art for use in cable outer sheaths. The addition of the lubricant can reduce friction and improve the flowability of the material; and this invention is not limited to one or more of calcium stearate, zinc stearate, and stearic acid listed below. As an example, the lubricant may be stearic acid, oxidized polyethylene wax, calcium stearate, zinc stearate, magnesium stearate, etc.
[0022] antioxidants The antioxidant used in this invention is a known antioxidant in the art that can be used for cable outer sheaths. The addition of the antioxidant can inhibit the oxidative degradation of the outer sheath and extend the service life of the cable. Furthermore, this invention is not limited to antioxidants 1076 and 168 listed below. As an example, the antioxidant may be antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 264, etc.
[0023] UV absorber The ultraviolet absorber used in this invention is a known ultraviolet absorber in the art that can be used for cable outer sheaths. The addition of the ultraviolet absorber can delay the aging of the cable caused by ultraviolet radiation. Furthermore, this invention is not limited to one or more of the ultraviolet absorbers UV-531, UV-327, and UV-328 listed below. As an example, the ultraviolet absorber may be ultraviolet absorber UV-531, UV-9, UV-327, and UV-328, etc.
[0024] Coupling agent The coupling agent used in this invention is a known coupling agent in the art that can be used for cable outer sheaths. The addition of the coupling agent can improve the dispersibility of the filler in the matrix and prevent agglomeration. Furthermore, this invention is not limited to the silane coupling agent KH-550 listed below. As examples, the coupling agent can be silane coupling agent KH-550, silane coupling agent KH-560, silane coupling agent KH-570, etc.
[0025] The present invention discloses a high-strength cable comprising a conductor, an insulation layer, and an outer sheath arranged sequentially from the inside out; the outer sheath comprises the following raw materials: polyethylene, ethylene-vinyl acetate copolymer, filler, toughening agent, lubricant, antioxidant, ultraviolet absorber, and coupling agent.
[0026] In the raw materials for the outer sheath of high-strength cables, the weight percentage of polyethylene is 70-85 parts, preferably 72-82 parts, and more preferably 75-80 parts.
[0027] In the raw materials for the outer sheath of high-strength cables, the ethylene-vinyl acetate copolymer accounts for 18 to 24 parts by weight, preferably 20 to 22 parts.
[0028] In the raw materials for the outer sheath of high-strength cables, the filler is 15 to 20 parts by weight, preferably 16 to 18 parts.
[0029] In the raw materials for the outer sheath of high-strength cables, the toughening agent comprises 8 to 14 parts by weight, preferably 10 to 12 parts.
[0030] In the raw materials for the outer sheath of high-strength cables, the weight percentage of lubricant is 0.8 to 1.6 parts, preferably 1 to 1.4 parts.
[0031] In the raw materials for the outer sheath of high-strength cables, the antioxidant contains 0.4 to 0.8 parts by weight, preferably 0.5 to 0.7 parts.
[0032] In the raw materials for the outer sheath of high-strength cables, the weight percentage of ultraviolet absorber is 0.3 to 0.7 parts, preferably 0.4 to 0.6 parts.
[0033] In the raw materials for the outer sheath of high-strength cables, the coupling agent comprises 0.8 to 1.5 parts by weight, preferably 1.0 to 1.2 parts.
[0034] Methods for preparing high-strength cables The present invention also provides a method for preparing the high-strength cable as described above, comprising: An insulation layer is set on the outside of the conductor to obtain the wire core; polyethylene, ethylene-vinyl acetate copolymer, coupling agent, filler, toughening agent, antioxidant, ultraviolet absorber and lubricant are added in sequence and mixed, and then extruded onto the surface of the wire core to obtain a high-strength cable.
[0035] To further illustrate the present invention, the following examples will provide a detailed description. The raw materials used in the following examples and comparative examples of the present invention are all commercially available products. Specifically, the polyethylene is high-density polyethylene, model 5000S; the ethylene-vinyl acetate copolymer is model 18J3; the polyolefin elastomer is model 8150; the liquid terpene resin has an acid value of 1.0 mg KOH / g and is model BL-118; the rosin triethylene glycol ester has an acid value of 20 mg KOH / g and is model BL-180; the needle-shaped wollastonite powder has an average diameter of 2 μm and an average length of 30 μm; the aluminosilicate fiber powder has an average diameter of 4 μm and an average length of 50 μm; the barium sulfate has an average particle size of 4 μm; and the fly ash precipitates have an average particle size of 10 μm.
[0036] Example 1 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 70 parts of polyethylene, 18 parts of ethylene-vinyl acetate copolymer, 0.8 parts of silane coupling agent KH-550, 15 parts of needle-shaped wollastonite powder, 8 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1), 0.3 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-531, and 0.8 parts of calcium stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0037] Example 2 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0038] Example 3 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 85 parts of polyethylene, 24 parts of ethylene-vinyl acetate copolymer, 1.5 parts of silane coupling agent KH-550, 20 parts of needle-shaped wollastonite powder, 14 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1), 0.6 parts of antioxidant 1076, 0.2 parts of antioxidant 168, 0.7 parts of ultraviolet absorber UV-328, and 1.6 parts of stearic acid are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0039] Example 4 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.2), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0040] Example 5 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.5), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0041] Example 6 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.8), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0042] Example 7 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of filler (acicular wollastonite powder, aluminum silicate fiber powder and barium sulfate in a mass ratio of 5:3:1.5), 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.5), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are mixed and extruded onto the surface of the wire core to obtain a high-strength cable.
[0043] Example 8 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of filler (acicular wollastonite powder, aluminosilicate fiber powder and fly ash beads in a mass ratio of 5:3:1.5), 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.5), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are mixed and extruded onto the surface of the wire core to obtain a high-strength cable.
[0044] Example 9 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of filler (acicular wollastonite powder, aluminosilicate fiber powder and fly ash beads in a mass ratio of 5:3:2), 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.5), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are mixed and extruded onto the surface of the wire core to obtain a high-strength cable.
[0045] Example 10 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of filler (acicular wollastonite powder, aluminosilicate fiber powder and fly ash beads in a mass ratio of 5:3:2.5), 12 parts of toughening agent (polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 6.5:2:1.5), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are mixed and extruded onto the surface of the wire core to obtain a high-strength cable.
[0046] Comparative Example 1 A method for manufacturing high-strength cables includes the following steps: An insulation layer is formed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer and liquid terpene resin in a mass ratio of 6.5:2), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0047] Comparative Example 2 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (liquid terpene resin and rosin triethylene glycol ester in a mass ratio of 2:1), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0048] Comparative Example 3 A method for manufacturing high-strength cables includes the following steps: An insulation layer is placed on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of toughening agent (polyolefin elastomer and rosin triethylene glycol ester in a mass ratio of 6.5:1), 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0049] Comparative Example 4 A method for manufacturing high-strength cables includes the following steps: An insulation layer is set on the outside of the conductor to obtain the wire core; 80 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 1.2 parts of silane coupling agent KH-550, 18 parts of needle-shaped wollastonite powder, 12 parts of polyolefin elastomer, 0.4 parts of antioxidant 1076, 0.1 parts of antioxidant 168, 0.3 parts of ultraviolet absorber UV-327, 0.2 parts of ultraviolet absorber UV-328, and 1.2 parts of zinc stearate are added sequentially and mixed, then extruded onto the surface of the wire core to obtain a high-strength cable.
[0050] Performance testing The elongation at break of the cable outer sheath at -40℃ was tested using the method in GB / T 2951.14-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 14: General Test Methods - Low Temperature Test". The tensile strength of the cable outer sheath was tested using the methods in GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 11: General Test Methods - Thickness and Dimensional Measurements - Mechanical Properties Test". A dumbbell-shaped specimen with a thickness of 2 mm was selected as the test sample. The performance of the cable outer sheaths obtained by each embodiment 1 to 10 and comparative examples 1 to 4 after testing is shown in Table 1 and Table 2.
[0051] Table 1. Low-temperature performance test results of the cable outer sheaths obtained in Examples 1-6 and Comparative Examples 1-4
[0052] 1. The cable outer sheaths prepared in Examples 1-6 have a higher elongation at break at -40°C than all comparative examples, indicating that the polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester work synergistically to improve the low-temperature resistance of the cable outer sheath, thereby improving the low-temperature resistance of the cable.
[0053] 2. The cable outer sheath prepared in Examples 4 and 5 achieved an elongation at break of 126% to 128% at -40°C, indicating that when the mass ratio of polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester is in the range of 6.5:2:1.2 to 1.5, the resulting cable has better low-temperature resistance.
[0054] Table 2. Test results of the strength performance of the cable outer sheaths obtained in Examples 5 and 7-10.
[0055] The tensile strength of the cable outer sheaths prepared in Examples 8-10 reached 23.5-24.8 MPa, which was higher than that in Examples 5 and 7. This indicates that the use of a compound of needle-shaped wollastonite powder, aluminosilicate fiber powder, and fly ash beads as fillers can improve the strength of the cable outer sheath. The tensile strength of the cable outer sheath prepared in Example 9 was even higher than that in Examples 8 and 10. This indicates that limiting the mass ratio of needle-shaped wollastonite powder, aluminosilicate fiber powder, and fly ash beads to 5:3:2 further improved the strength of the cable outer sheath.
[0056] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-strength cable, characterized in that, It includes a conductor, an insulating layer, and an outer sheath arranged sequentially from the inside out; the outer sheath comprises the following raw materials: polyethylene, ethylene-vinyl acetate copolymer, filler, toughening agent, lubricant, antioxidant, ultraviolet absorber, and coupling agent; The toughening agent includes polyolefin elastomer, liquid terpene resin and rosin triethylene glycol ester.
2. The high-strength cable according to claim 1, characterized in that, The mass ratio of the polyolefin elastomer, liquid terpene resin, and rosin triethylene glycol ester is 6.5:2:1.2~1.
5.
3. A high-strength cable according to claim 1, characterized in that, The outer sheath comprises the following raw materials in parts by weight: 70-85 parts polyethylene, 18-24 parts ethylene-vinyl acetate copolymer, 15-20 parts filler, 8-14 parts toughening agent, 0.8-1.6 parts lubricant, 0.4-0.8 parts antioxidant, 0.3-0.7 parts ultraviolet absorber, and 0.8-1.5 parts coupling agent.
4. A high-strength cable according to claim 1, characterized in that, The filler includes one or more of the following: needle-shaped wollastonite powder, aluminum silicate fiber powder, barium sulfate, and fly ash pellets.
5. A high-strength cable according to claim 4, characterized in that, When the filler comprises needle-shaped wollastonite powder, aluminosilicate fiber powder, and fly ash pellets, the mass ratio of the needle-shaped wollastonite powder, aluminosilicate fiber powder, and fly ash pellets is 5:3:1.5~2.
5.
6. A high-strength cable according to claim 1, characterized in that, The lubricant includes one or more of calcium stearate, zinc stearate, and stearic acid.
7. A high-strength cable according to claim 1, characterized in that, The antioxidants include antioxidant 1076 and antioxidant 168.
8. A high-strength cable according to claim 1, characterized in that, The ultraviolet absorber includes one or more of ultraviolet absorber UV-531, ultraviolet absorber UV-327, and ultraviolet absorber UV-328.
9. A high-strength cable according to claim 1, characterized in that, The coupling agent includes a silane coupling agent.
10. A method for preparing a high-strength cable, used to prepare the high-strength cable according to any one of claims 1 to 9, characterized in that, Includes the following steps: An insulating layer is formed on the outside of the conductor to obtain the wire core; polyethylene, ethylene-vinyl acetate copolymer, coupling agent, filler, toughening agent, antioxidant, ultraviolet absorber and lubricant are added in sequence and mixed, and then extruded onto the surface of the wire core to obtain a high-strength cable.